Hukum Kasih dalam Teologi Paulus dan Dalihan Na Tolu: Membangun Etika Kristiani Kontekstual di Tanah Batak - Artariah Artariah; Suang Manik; Immanel Sidauruk (Sepakat : Jurnal Pastoral Kateketik, 2024)
Love is the main principle in Christianity taught by Jesus and emphasized by the Apostle Paul as the fulfillment of the Law. In the context of Batak society, the Dalihan Na Tolu social system regulates social relations based on the principles of honor, solidarity, and responsibility. This research aims to analyze how the law of love in Paul's theology can be integrated with the principles of Dalihan Na Tolu to build contextual Christian ethics in Batak land without losing the essence of the gospel. This research uses a qualitative method with a theological and ethnographic study approach. Literature studies were conducted on biblical texts, Pauline theological sources, and references to Batak culture. Hermeneutic analysis was used to understand the concept of the law of love in Paul's theology, while a study of Dalihan Na Tolu was conducted to identify its relevance to Christian ethics. The results show that there are similar values between the law of love in Paul's theology and the principles of Dalihan Na Tolu, especially in terms of love, respect and solidarity. However, some aspects of Dalihan Na Tolu need to be criticized, especially in terms of social hierarchy that can lead to injustice. Therefore, cultural transformation is needed so that the principle of love taught in the Bible can become the basis of Christian ethics that are relevant to Batak society. This research contributes to the development of contextual theology and provides insight for the church and Batak community in applying the law of love in social and traditional life.